Navigating Challenges: How Divorce Affects the Quality of Children's Education - Suprianto, Nanang; Syukri, Syukri; Suriyani, Erma (Jurnal Ilmiah Profesi Pendidikan, 2024)
Divorce is a complex life event that often profoundly affects various aspects of family life, including children's education. This study aims to explore the impact of divorce on the quality of children's education, considering both academic and socio-emotional dimensions. A mixed-methods approach was employed, combining quantitative surveys and qualitative interviews. The participants consisted of parents and teachers from diverse socio-economic backgrounds, providing a comprehensive understanding of the phenomenon. Surveys were utilized to collect quantitative data on academic performance, attendance, and behavioral changes among children from divorced families. Additionally, in-depth interviews were conducted to gather qualitative insights into the emotional and social adjustments experienced by these children. Data were analyzed using statistical techniques for quantitative data and thematic analysis for qualitative data. The findings reveal multifaceted impacts of divorce on children's education, encompassing academic challenges, emotional distress, and changes in social dynamics. These results underscore the need for targeted interventions and support systems within educational settings to address the unique needs of children affected by divorce.